2016
DOI: 10.1182/blood.v128.22.221.221
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Global Registration Trial of the Efficacy and Safety of CTL019 in Pediatric and Young Adults with Relapsed/Refractory Acute Lymphoblastic Leukemia (ALL)

Abstract: A single-center trial of CD19 directed, lentiviral transduced chimeric antigen receptor (CAR) T cells (CTL019) for relapsed and refractory (r/r) B-ALL pediatric patients showed rates of CR >90% with prolonged CAR T cell persistence/CR without further therapy in the majority of patients infused (Maude NEJM 2014). We report here the feasibility, safety and efficacy of the first multicenter global pivotal registration CAR T cell trial. Features of this trial include: i) the first trial in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…However, neurotoxicity does not always occur with the presence of systemic CRS, and the mechanism remains unclear. In our study, reversible neurotoxicity was only observed in 1 patient (5.6%) after hCART19s infusion, and the incidence rate of neurotoxicity was lower as compared to reported data by other studies . In addition, elevated amplification of CAR‐T cells and increased cytokines were detected in CSF, which is in accordance with other reports .…”
Section: Discussionsupporting
confidence: 89%
“…However, neurotoxicity does not always occur with the presence of systemic CRS, and the mechanism remains unclear. In our study, reversible neurotoxicity was only observed in 1 patient (5.6%) after hCART19s infusion, and the incidence rate of neurotoxicity was lower as compared to reported data by other studies . In addition, elevated amplification of CAR‐T cells and increased cytokines were detected in CSF, which is in accordance with other reports .…”
Section: Discussionsupporting
confidence: 89%
“…CARs, which consist of the combination of an antibody and a TCR, are antigen specific and their activation is not dependent on MHC expression on tumor cells. CAR-T cells therapy has been particularly successful in hematologic cancers, including the CTL019 for young adult B-ALL patients 17 (Grupp, 2016) and the CT019 for refractory aggressive NHL. 18…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
“…The field is rapidly evolving from multiple aspects and is the focus of several pre‐clinical and clinical efforts (Rosenberg & Restifo, ). The results of a pivotal multicentre registration trial for R/R ALL paediatric and young adult patients treated with a CD19‐directed lentivirus transduced CAR‐T cell (CTL019, ELIANA [Efficacy and safety of CTL019 in paediatric patients with R/R B‐cell ALL] trial) were recently presented and demonstrated the feasibility, safety and high efficacy of this approach (Grupp et al , ).…”
Section: The Approach To Relapsed/refractory Patients With Allmentioning
confidence: 99%